THE ROLE OF ARTISTIC DESCRIPTION IN THE EXPRESSION OF CONTENT : (based on the stories of Seyid Hussein) - Tahmina Valiyeva (International Journal of Innovative Technologies in Social Science, 2021)
The artistic description, with its quality, gives the text a new poetic character and provides an interpretation of the content in the aesthetic structure. The description not only increased the artistic and aesthetic quality of literary works, but also enriched them in terms of language and style. Like many writers who took advantage of the descriptive potential of the Azerbaijani language, which is characteristic of the early twentieth century, Seyid Hussein also created successful poetic figures. Based on his creative style, he formed a unique style of description, and in this regard, managed to create authentic works at the level of figurative literary and artistic language. In Seyid Hussein’s stories, the description is multifaceted and has become an expression form of different attitudes, feelings and thoughts. Using description methods, the writer not only narrates the subject, does not draw the external and internal qualities of the images, does not give a poetic picture of place and time. He delivers to the reader the psychological moods of characters, their effects on their situations and actions, feelings and thoughts to the reader in a poetic language. Artistic description played the role of illuminating the dark worlds of the characters in the stories.